Pelaksanaan Kesehatan dan Keselamatan Kerja dan Jaminan Sosial Bpjs Ketenagakerjaan bagi Pekerja di Kantor Notaris - Ilwira Fakhrurrazi Lubis (Syntax Corporation Indonesia, 2023)
Notary office is one type of workplace that requires the implementation of occupational health and safety as well as social security / BPJS employment for its workers. This study aims to analyze the implementation of occupational health and safety as well as social security/BPJS employment for workers in notary offices. This research is a normative juridical research that uses legal principles, laws and doctrines as the main legal material, even the main law is analyzed and interpreted against secondary legal material in the form of literature or library material, to find research results according to the problems posed. The results showed that the implementation of occupational health and safety as well as social security/employment BPJS for workers in notary offices still needs to be improved. Some factors that influence the implementation include employee and management awareness of the importance of occupational health and safety, company policies that support the implementation of occupational health and safety, and the availability of funds to finance social security/employment BPJS. This study recommends the need to increase employee and management awareness of the importance of occupational health and safety as well as social security/employment BPJS for workers in notary offices. This can be done through socialization and training, implementation of company policies that support the implementation of occupational health and safety as well as social security/BPJS employment, and the allocation of sufficient funds to finance the program. Thus, it is expected to create a healthy, safe, and social protection environment for workers in notary offices.